STUDI KARAKTERISTIK ELEKTRIK MODUL PIEZOELEKTRIK TERHADAP VARIASI BEBAN RESISTIF SEBAGAI SUMBER ENERGI ALTERNATIF TERBARUKAN - Marvil Rafael Rondonuwu; Valentino Goerge Muaya; Maruto Swatara Loegimin; Sonny R. Kasenda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mechanical energy harvesting from human footsteps is a potential solution for supplying micro-power to autonomous electronic devices. This study aims to investigate the electrical characteristics of PZT (Lead Zirconate Titanate) piezoelectric modules arranged in a parallel configuration of 20 units to respond to a mechanical load of 100 kg. The main focus of this research is to analyze the effect of low resistive load variations from 10 Ω to 110 Ω on power transfer efficiency. The experimental method was carried out by applying a static load of 100 kg to the piezoelectric array connected to a full-bridge rectifier circuit using 1N4007 diodes and a 47 µF filter capacitor. The output voltage was then measured across six variations of resistive loads using a digital multimeter, with three repetitions at each measurement point to ensure data validity. The results show that increasing the load resistance is directly proportional to the increase in output voltage, but inversely proportional to the generated current. The Maximum Power Point (MPP) was identified at a resistive load of 90 Ω with a power output of 33.64 mW. This phenomenon demonstrates that the parallel configuration of the piezoelectric array effectively reduces the internal impedance of the system, allowing optimal energy transfer within a low-load range.